2019
DOI: 10.1002/ppp3.10068
|View full text |Cite
|
Sign up to set email alerts
|

Network modelling, citizen science and targeted interventions to predict, monitor and reverse bee decline

Abstract: Societal Impact Statement The global decline in pollinating insect populations has rightly received widespread news coverage as it imperils ecosystem function and human food security. Reversing and addressing this decline is an urgent global priority. However, in many locations we do not know what species are present, how large or small species populations are, or what types of specific resources the populations require. By adopting novel network analyses approaches and by working with monitoring programs, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Those benefits contribute to the popularity of citizen science projects (CSP) reflected by countless research topics published within the last years [5][6][7]. Although insects in general potentially evoke negative perceptions in humans [8,9], pollinators like bumble bees and butterflies are attractive groups for CSP [10][11][12][13][14][15]. Most CSP focus on creating data sets of species distribution records [3], which constitute the baseline of abundance studies [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Those benefits contribute to the popularity of citizen science projects (CSP) reflected by countless research topics published within the last years [5][6][7]. Although insects in general potentially evoke negative perceptions in humans [8,9], pollinators like bumble bees and butterflies are attractive groups for CSP [10][11][12][13][14][15]. Most CSP focus on creating data sets of species distribution records [3], which constitute the baseline of abundance studies [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In landscape architecture terms such as third landscape (Clément, 2014) or intermediate landscape (or intermediate nature; Desvigne, 2009) are used for such abandoned interstitial land. Urban wastelands have been a focus of urban botany early on (Lachmund, 2003). Through their often relatively large size and lack of use, they often harbor rare and relatively large-sized wild species, and they are wild in the sense that natural processes such as colonization, succession, and disturbance regimes are not (or only weakly) shaped through deliberate human intervention.…”
Section: Wastelandsmentioning
confidence: 99%
“…They struggle with insect identification and cannot differentiate between a pest insect and a beneficial one. Research done by Lander (2020) showed how these types of projects could impact participants in behavioral and cognitive ways. They learn as they participate, and as a result their behavior changes to reflect what they learn.…”
Section: Project Goalsmentioning
confidence: 99%